External Validation of the Early Prediction of Functional Outcome After Stroke Prediction Model for Independent Gait at 3 Months After Stroke - Veerbeek, Janne M.; Pohl, Johannes; Held, Jeremia P. O.; Luft, Andreas R. (Frontiers in Neurology, 2022)
Introduction: The Early Prediction of Functional Outcome after Stroke (EPOS) model for independent gait is a tool to predict between days 2 and 9 poststroke whether patients will regain independent gait 6 months after stroke. External validation of the model is important to determine its clinical applicability and generalizability by testing its performance in an independent cohort. Therefore, the aim of this study was to perform a temporal and geographical external validation of the EPOS prediction model for independent gait after stroke, but with the endpoint being 3 months instead of the original 6 months poststroke. Methods: Two prospective longitudinal cohort studies consisting of first-ever stroke patients admitted to a Swiss hospital stroke unit. Sitting balance and strength of the paretic leg were tested at days 1 and 8 poststroke in Cohort I and at days 3 and 9 in Cohort II. Independent gait was assessed 3 months after symptom onset. The model’s performance in terms of discrimination (Area under the Receiver Operator Characteristic Curve; AUC), classification, and calibration was assessed. Results: In Cohort I (N=39, median age 74 years, 33% female, median National Institutes of Health Stroke Scale [NIHSS] 9), the AUC (95% confidence interval) was 0.675 (0.510, 0.841) at day 1 and 0.921 (0.811, 1.000) at day 8. For Cohort II (N=78, median age 69 years, 37% female, median NIHSS 8), this was 0.801 (0.684, 0.918) at day 3 and 0.846 (0.741, 0.951) at day 9. Discussion and conclusion: External validation of the EPOS prediction model for independent gait 3 months after stroke resulted in an acceptable performance from day 3 onwards in mild-to-moderately affected first-ever stroke patients without severe pre-stroke disability. The impact of applying this model in clinical practice should be investigated within this subgroup of stroke patients. To improve generalizability to recurrent stroke patients and those with more severe, neurological comorbidities, the performance of the EPOS model within these patients should be determined across different geographical areas.